Underlying risk factors and their relationship with extent of coronary vessel involvement in patients undergoing coronary angiography in North of Iran - Fahimeh Kazemian; seyed farzad jalali; Karimolah Hajian-Tilaki; Afsaneh Arzani; Kamyar Amin (Babol University of Medical Sciences, 2018)
Background: Coronary artery disease (CAD) is one of the most progressive and life-threatening diseases and is the first leading cause of death affecting both genders in Iran. The present study aimed to determine the extent of coronary vessel involvement and relevant relationship with several underlying risk factors. Methods: In this cross-sectional study, 1452 patients undergoing angiography who met the inclusion criteria were recruited consecutively in Babol, Iran during 2016. Data collection was performed through a questionnaire including demographic and clinical characteristics and information on underlying diseases via an interview with the patient and looking into the patients' records. Results: Of these patients, 459 (31.6%) had normal coronary arteries, 220 (15.1%) suffered from non-obstructive CAD and 773 (53.3%) had one, two or three-vessel obstructive involvement. The results of multiple logistic regression showed that the chances of having coronary artery involvement in patients with diabetes (OR=1.55, p=0.012), age> 60 years old (OR=3.52, P=0.001), male gender (OR=2.54, P=0.001), history of heart attack (OR=3.16, P=0.001), and history of hospitalization because of cardiac problem (OR=1.51, P=0.021) significantly increased. Conclusions: Diabetes, male gender, age over 60 years old, history of myocardial infarction and history of hospitalization due to cardiac problem were related to the extent of coronary vessels involvement. Therefore, it is recommended to practice preventive measures more extensively in this regard.